The Urgency of Civil Code Reform That Is Responsive to the Needs of Modern Digital Business - Siti Munawaroh; Nuruz Zakiyatul Mufidah; Wahyu Tris Haryadi; Alarico M. Tilman (Trunojoyo Madura University, 2025)
The rapid advancement of Indonesia’s digital economy and e-commerce sector has significantly contributed to economic growth, job creation, and financial inclusion. Nevertheless, the prevailing civil law framework, which remains rooted in the colonial-era Indonesian Civil Code (KUH Perdata), is increasingly viewed as inadequate for regulating electronic transactions, consumer protection, and digital business innovation. The Electronic Information and Transactions Law (UU ITE) also fails to provide comprehensive regulation in these areas. Therefore, modernizing the Civil Code is imperative to accommodate the needs of digital transactions, ensure legal certainty, and enhance national competitiveness. This study employs a normative legal research method, utilizing statutory and conceptual approaches, and examines legal doctrines, theories, and expert opinions to analyze the necessity of civil law reform in the digital era. The findings indicate that the rigidity and ambiguity of the current Civil Code create legal vacuums, particularly concerning electronic contracts, smart contracts, and digital data protection,substantive reform of the Civil Code.